2017
DOI: 10.1590/0074-02760170061
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease ecoepidemiology and environmental changes in northern Minas Gerais state, Brazil

Abstract: BACKGROUND Triatoma sordida and Triatoma pseudomaculata are frequently captured triatomine species in the Brazilian savannah and caatinga biomes, respectively, and in Brazilian domiciles.OBJECTIVESThis study identified eco-epidemiological changes in Chagas disease in northern Minas Gerais state, Brazil, and considered the influence of environmental shifts and both natural and anthropogenic effects.METHODSDomicile infestation and Trypanosoma cruzi infection rates were obtained from triatomines and sylvatic rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Chagas Cardiomyopathy is an important cause of HF in Latin America 20 . This corroborates the results of this study, which was performed in a Brazilian state that is endemic for Chagas Disease and has areas of low socioeconomic status and low Human Development Index 21 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Chagas Cardiomyopathy is an important cause of HF in Latin America 20 . This corroborates the results of this study, which was performed in a Brazilian state that is endemic for Chagas Disease and has areas of low socioeconomic status and low Human Development Index 21 …”
Section: Discussionsupporting
confidence: 88%
“…20 This corroborates the results of this study, which was performed in a Brazilian state that is endemic for Chagas Disease and has areas of low socioeconomic status and low Human Development Index. 21 Even though the median age of HT recipients in this study represents a middle-aged adult, 56.5% of the sample were already retired and only 24.5% were working. A lower level of education, despite being present in most patients, was not statistically related to survival.…”
Section: Discussionmentioning
confidence: 79%
“…Over the years, T. pseudomaculata , typical of semi‐arid climate and vegetation, has established itself in several Brazilian regions, showing itself to be a species in transition (Assis et al., 2009; Dias et al, 2000; Vianna et al., 2017; Oliveira‐Filho et al., 2000). Previous research has already recorded the occurrence of this species in the north of Minas Gerais, and in recent years, an increase in its population has been verified due to the increase in temperature and aridification of this region (Dias et al., 2005; Vianna et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the Municipality of Caxias, State of Rio de Janeiro, houses were investigated, and the presence of triatomines of the genus Triatoma was reported. In rural Jurema, Minas Gerais, it was observed that the species Triatoma sordida continues to colonize the houses [19]. In the municipalities of Araçatuba and Birigui, in the State of São Paulo, specifically in its urban area, the frequent presence of Rhodnius neglectus in apartment buildings has been reported, including signs of colonization [20].…”
Section: Discussionmentioning
confidence: 99%